PENGARUH LATIHAN ALTERNATE LEG BOUND TERHADAP HASIL DAYA LEDAK OTOT TUNGKAI PADA SISWA KELAS XI SMAKF IKASARI PEKANBARU - Ramadhan, Ikwal; Ramadi, Ramadi; Juita, Ardiah (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: Observations in the field and on the basis of statements made to the teacher who has authority during the learning activities, it is still said that Class XI SMK IKASARI Pekanbaru is weak in terms of his strength. This is apparent from the large number of students who are unable to reach the standards set by the teacher. In addition, rejecting students also saw that they looked slow, so that the results of the jump were short. The aim of this study was to determine: "The effect of alternative leg-binding exercise on explosion of leg muscles in class XI students of SMKF IKASARI Pekanbaru. The population of this research is 11th class students of SMK Ikasari Pekanbaru. This research uses a total sampling technique, in which the entire population is sampled.The instrument in this study was broad jump.The data obtained were analyzed using t-test.On the basis of data analysis and discussion it can be concluded that there is an effect of Artenate leg-bound training on the leg muscle explosive power of class XI students from Pekanbaru IKASARI SMAKF, proven by the results of tcount 5,566> t table 1,812 at α = 0.05 This proves that by doing Artenate leg-bound exercises, the leg muscle explosive power produce better results.Key Words: Artenate Leg Bound, Leg Muscle Explosion Power